Tailored nutrition strategies for Paralympic athletes: addressing unique energy, nutrients, and hydration needs to enhance performance and health - Ghazzawi, H.; Al-Aqaili, R.; Khataybeh, B.; Al-Aittan, F.; Hamaideh, S.; Alhalaiqah, T.; Amawi, A.; Trabelsi, K.; Jahrami, H.; AlHaj Hasan, M. (Frontiers in Nutrition, 2024)
Background: This study used a systematic evaluation and meta-analysis to determine how the timing of nutritional supplements affected the recovery from post-exercise weariness. A vital component of enhancing athletic performance and advancing health is post-exercise recovery, where nutritional supplements are crucial. Although it has been demonstrated that supplementing timing may affect recovery outcomes, there is conflicting evidence about the best time to take supplements.